2021
DOI: 10.3389/fpsyg.2021.687179
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Validation of a Cognitive Diversity Scale for Chinese Academic Research Teams

Abstract: Cognitive diversity is an important concept stemming from western management research in the 1990s. With the rapid development of science and technology, there is a growing interest in the composition of an academic research team, such as team diversity. However, there is no tool available for measuring team cognitive diversity (TCD) for academic research teams. Based on Van der Vegt’s theoretical model of TCD, an Academic Research Team Cognitive Diversity Scale (ATCDS) is developed and validated for an academ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In group performance studies that examined cognitive diversity as an independent variable, Dong et al (2021) found that academic performance in research teams is fostered by cognitive diversity, while Liao and Long (2016) showed that group performance increases with high alertness (as a combination of information accumulation, transformation, and selection) arising from high cognitive diversity. Cognitive diversity positively affects group effectiveness through group learning, and an inclusive climate in terms of group discussion and decision processes (Chow, 2018; Mathuki & Zhang, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In group performance studies that examined cognitive diversity as an independent variable, Dong et al (2021) found that academic performance in research teams is fostered by cognitive diversity, while Liao and Long (2016) showed that group performance increases with high alertness (as a combination of information accumulation, transformation, and selection) arising from high cognitive diversity. Cognitive diversity positively affects group effectiveness through group learning, and an inclusive climate in terms of group discussion and decision processes (Chow, 2018; Mathuki & Zhang, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Ten articles examined the relationship between group cognitive (style) diversity and creativity. Dong et al (2021) evaluated cognitive diversity in academic research teams and reported a positive association with team creativity. Kurtzberg (2005) found that cognitive diversity could benefit creative performance but reduce positive affect, satisfaction, and group members' feelings about their creative endeavor.…”
Section: Topicsmentioning
confidence: 99%